2014
DOI: 10.1002/art.38624
|View full text |Cite
|
Sign up to set email alerts
|

Bone‐ and Cartilage‐Protective Effects of a Monoclonal Antibody Against Colony‐Stimulating Factor 1 Receptor in Experimental Arthritis

Abstract: Objective. Colony-stimulating factor 1 receptor (CSF-1R) essentially modulates monocyte proliferation, migration, and activation, which are considered important for the pathogenesis of rheumatoid arthritis (RA). We undertook this study to determine CSF-1R expression in human RA as well as the efficacy of a specific anti-CSF-1R monoclonal antibody (AFS98) in 2 different animal models of RA.Methods. CSF-1R expression was examined in blood, synovium, and bone samples from RA patients, osteoarthritis (OA) patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 56 publications
2
52
0
Order By: Relevance
“…Conversely, its neutralisation reduces the severity of established CIA 46. Finally, recent data support the evidence that blockade of the M-CSF receptor reduces inflammation in CIA and abrogates cartilage damage and bone erosion 47. Moreover, inhibitors of M-CSF and its receptor are in preclinical development for the treatment of RA and other autoimmune diseases 47 48…”
Section: Discussionmentioning
confidence: 71%
“…Conversely, its neutralisation reduces the severity of established CIA 46. Finally, recent data support the evidence that blockade of the M-CSF receptor reduces inflammation in CIA and abrogates cartilage damage and bone erosion 47. Moreover, inhibitors of M-CSF and its receptor are in preclinical development for the treatment of RA and other autoimmune diseases 47 48…”
Section: Discussionmentioning
confidence: 71%
“…Macrophages are key contributors to highly prevalent immunological diseases [35] such as rheumatoid arthritis, inflammatory bowel disease, and demyelinating neurological diseases [68]. Macrophages also play key homeostatic roles in non-immune tissues and contribute to diseases such as atherosclerosis and cancer [911].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these models indicate that CSF-1 neutralization can result in fewer inflammatory macrophages in a lesion, with perhaps significance for clinical approaches (11), but is in disagreement with the findings of others (27,31). A number of studies have found that CSF-1R and CSF-1 neutralization/depletion can reduce inflammatory/autoimmune disease (2,10,29,(69)(70)(71)(72)(73)(74), suggesting that targeting of this system may provide therapeutic options. One possible mechanism for the reduction in inflammatory MPS populations found in the earlier models after CSF-1 neutralization is that the removal of a resident macrophage population by such an approach lessens the signal(s) governing overall cellular infiltration; in support of this concept, in the AIP model, fewer CD115 2 cells were also noted.…”
Section: Discussionmentioning
confidence: 94%